Eksplorasi Berpikir Aljabar Siswa Kelas V dalam Menyelesaikan Soal Pola Bilangan - Maharani, Windy Anggita; Masduki, Masduki (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
This study aims to investigate the algebraic thinking skills of fifth grade elementary school students in solving functional dimension problems. The type of research is descriptive qualitative. The subjects in this study were 131 grade 5 students from two private elementary schools in Surakarta, Central Java, Indonesia. The data collection instrument used was 5 questions on the dimension function algebraic thinking test adopted from Raslton which consisted of 2 numerical pattern questions and 3 picture pattern questions. Prior to use, the questions were first validated by three elementary school mathematics learning experts and tested on 10 students who were not included as research subjects. This research is limited to data analysis of 89 students who belong to the category of moderate algebraic thinking skills obtained from the test results. Data analysis was carried out by analyzing students' answer documents in solving algebraic thinking test questions. Document analysis is focused on solving steps and strategies used to solve problems. The results showed that students were more able to solve linear patterns than nonlinear patterns. Students are also more able to solve numerical patterns than picture patterns. In addition, the strategy used to solve numerical patterns is to determine multiples of numbers and identify the differences between terms in the pattern. Whereas in solving of picture patterns, the strategy used is to draw patterns and identify differences between terms in patterns. This study concluded that most of the subjects in the moderate category were able to demonstrate algebraic thinking skills in functional dimensions.